2022
DOI: 10.1021/acschembio.1c00880
|View full text |Cite
|
Sign up to set email alerts
|

Subsite Ligand Recognition and Cooperativity in the TPP Riboswitch: Implications for Fragment-Linking in RNA Ligand Discovery

Abstract: RNA molecules can show high levels of cooperativity in their global folding and interactions with divalent ions. However, cooperativity at individual ligand−RNA interaction sites remains poorly understood. Here, we investigated the binding of thiamine and methylene diphosphonic acid (MDP, a soluble structural analogue of pyrophosphate) to the thiamine pyrophosphate riboswitch. These ligands each bind weakly at proximal subsites, with 10 μM and 1 mM affinities, respectively. The affinity of MDP moderately impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…While structure-based computational methods like molecular docking are regularly used for protein targets, most identified RNA-binding small molecules, however, emerged from high-throughput or fragment-screening campaigns and derivatization of a known ligand or serendipity rather than structure-based design by molecular docking. , One challenge in this regard is the low number of available 3D RNA structures compared to the number of proteins deposited in the protein data bank (PDB), often additionally struggling with low resolution. However, these structures already show clearly that the limited chemical diversity of just four RNA bases compared to 20 canonical amino acids in proteins can still result in many different folds, for example, hairpins, G-quadruplexes, multiway junctions, (pseudo)­knots, L-shaped tRNAs, triple helices, ribozymes, and the ribosome complex .…”
Section: Introductionmentioning
confidence: 99%
“…While structure-based computational methods like molecular docking are regularly used for protein targets, most identified RNA-binding small molecules, however, emerged from high-throughput or fragment-screening campaigns and derivatization of a known ligand or serendipity rather than structure-based design by molecular docking. , One challenge in this regard is the low number of available 3D RNA structures compared to the number of proteins deposited in the protein data bank (PDB), often additionally struggling with low resolution. However, these structures already show clearly that the limited chemical diversity of just four RNA bases compared to 20 canonical amino acids in proteins can still result in many different folds, for example, hairpins, G-quadruplexes, multiway junctions, (pseudo)­knots, L-shaped tRNAs, triple helices, ribozymes, and the ribosome complex .…”
Section: Introductionmentioning
confidence: 99%
“…To further examine reference-subtracted SPR, we examined a set of compounds known to bind each of our RNA targets (Table S1). For the TPP riboswitch, the compounds examined bind with nanomolar to millimolar equilibrium dissociation constants, as measured by ITC. , We also examined TPP and its derivative thiamine, for which the binding affinities have been measured by numerous biophysical methods. ,,, For the SAM-III riboswitch RNA, we examined SAM and S -adenosyl homocysteine (SAH). SAM binds with sub-μM affinity, as measured by ITC, size exclusion filtration, and fluorescence quenching of a 2-aminopurine-substituted RNA. , Using the reported 2-aminopurine fluorescence assay, we measured a K D for SAH of 80 μM.…”
Section: Resultsmentioning
confidence: 99%
“…For the TPP riboswitch, the compounds examined bind with nanomolar to millimolar equilibrium dissociation constants, as measured by ITC. 31,45 We also examined TPP and its derivative thiamine, for which the binding affinities have been measured by numerous biophysical methods. 7,14,19,46 For the SAM-III riboswitch RNA, we examined SAM and Sadenosyl homocysteine (SAH).…”
Section: Resultsmentioning
confidence: 99%
“…Zeller and coworkers have recently shown that many RNAs bind their ligands via multiple subsites, which are regions of a binding pocket that contact a ligand in an independent or cooperative manner ( Zeller et al, 2022b ). Besides high-affinity RNA binding can occur even when subsite binding shows only modest cooperative effects and when the linking coefficient is unfavorable.…”
Section: Selectivity and Specificity Of Binding For Rnas Moleculesmentioning
confidence: 99%